Searching for correlation between global sustainability policy growth and growth in sustainability accounting research - Collins C. Ngwakwe (The journal of accounting and management, 2017)
This research examined whether accounting research responds to changing world policies toward sustainability ideology to remain relevant as a dynamic discipline. The paper became pertinent to highlight the extent to which accounting profession is imbued with the resilience to respond to sustainability through research. The paper applied a mixed method of review and quantitative empirical analysis. Sustainability-accounting research output data were collected from the Google Scholar. Sustainability policy initiatives were collected from the United Nations Framework Convention on Climate Change (UNFCCC) climate policy archive from 1989 - 2015. The co-integration and OLS regression statistics were applied to evaluate if the growth in sustainability accounting research correlates with the global growth in sustainability policy initiatives. The co-integration test showed a long-term correlation between the variables. Also, tested at an alpha of 0.05, results from the OLS regression analysis showed that an increase in sustainability and/or environmental accounting research has a significant correlation with the growing trend in global sustainability policy initiatives at a P=0.005 which is less than 0.05. The paper concludes that accounting research is being resilient to growing sustainability policy initiatives. The paper recommends further research to examine the extent to which sustainability accounting research has influenced a pragmatic change in corporate sustainability behaviour.
2668125-0; 2392-8778; The journal of accounting and management; 718053745